EXPERT APPROACH FOR ANALYSING A LOGISTICS CONTROL SYSTEM AND QUALITY MANAGEMENT IN THE CONDITIONS OF SMALL AND MEDIUM SERIAL PRODUCTION: EXPERT APPROACH FOR ANALYSING A LOGISTICS CONTROL SYSTEM AND QUALITY MANAGEMENT IN THE CONDITIONS OF SMALL AND MEDIUM SERIAL PRODUCTION - Yankova-Yordanova, Yordanka; Kodzheykova, Veselina (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The organization and management of technological production is a complex and very imaginative process which combines economic, technical, organizational and highly efficient solutions. For this purpose, concepts are developed in order to define the logistical goals related to the purchase, production, distribution and disposal of the batch production. As a whole, it formulates logistics systems directly influencing organizational decisions. The management and control of modern logistics systems is based on many hierarchically distributed, organizational levels.[9] On these grounds, the set logistic goals must solve the problems that have to do with the organization and management of production processes.